Imitation in heterogeneous populations - Hedlund, Jonas; Oyarzun, Carlos (Discussion paper series, 2016)
We study a boundedly rational model of imitation when payoff distributions of actions differ across types of individuals. Individuals observe others’ actions and payoffs, and a comparison signal. One of two inefficiencies always arises: (i) uniform adoption, i.e., all individuals choose the action that is optimal for one type but sub-optimal for the other, or (ii) dual incomplete learning, i.e., only a fraction of each type chooses its optimal action. Which one occurs depends on the composition of the population and how critical the choice is for different types of individuals. In an application, we show that a monopolist serving a population of boundedly rational consumers cannot fully extract the surplus of high-valuation consumers, but can sell to consumers who do not value the good.
Keywords: Arbeitspapier; Graue Literatur